Analisis Pengaruh Kinerja Keuangan Terhadap Pertumbuhan Ekonomi Dan Dampaknya Pada Pengangguran Di Pulau Jawa - Billy Vidhya Rumbobiar; Citra Sukmadilaga (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to analyze the impact of financial performance on economic growth and its effects on unemployment (a case study of each province in Java Island for the period 2014-2022). This study uses a population from 6 provinces with a sample size of 54 individuals. The sampling method employed in this research is non-random (purposive sampling). The hypotheses in this study are tested using panel data regression assisted by Eviews 12.0 software. Financial performance is measured based on the regional financial independence ratio, the effectiveness ratio, and the regional financial efficiency ratio. Economic growth and the unemployment rate are calculated as ratios by comparing the current year to the previous year. The research results indicate that financial performance, consisting of the regional financial independence ratio, the effectiveness ratio, and the regional financial efficiency ratio, significantly influence economic growth. The independence ratio, efficiency ratio, and economic growth do not significantly affect the unemployment rate. The effectiveness ratio significantly affects the unemployment rate. The independence ratio, effectiveness ratio, and efficiency ratio significantly influence economic growth through the unemployment rate.